The Great Thanksgiving Escape - Fearing, Mark (Somerville, Massachusetts : Candlewick Press, 2014)
It's another Thanksgiving at Grandma's. Gavin expects a long day of boredom and being pestered by distantly related toddlers, but his cousin Rhonda has a different idea: make a break for it - out of the kids' room to the swing set in the backyard! Gavin isn't so sure, especially when they encounter vicious guard dogs (in homemade sweaters), a hallway full of overly affectionate aunts, and worse yet, the great wall of butts! Will they manage to avoid the obstacles and find some fun before turkey time? Or will they be captured before they've had a taste of freedom?
Keywords: Thanksgiving Day -- Juvenile fiction; Families -- Juvenile fiction; Thanksgiving Day -- Fiction; Families -- Fiction; Humorous Stories